Synthesis and antiangiogenic activity of new silybin galloyl esters - Gažák, Radek; Valentová, Kateřina; Fuksová, Kateřina; Marhol, Petr; Kuzma, Marek; Medina, Miguel Ángel; Oborná, Ivana; Ulrichová, Jitka; Křen, Vladimír (Journal of medicinal chemistry, 2011)
The synthesis of various silybin monogalloyl esters was developed, and their antiangiogenic activities were evaluated in a variety of in vitro tests with human umbilical vein endothelial cells (HUVECs). A structure-activity relationship (SAR) study found the regioselectivity of the silybin galloylation to be highly significant. Silybin (as an equimolar mixture of two diastereomers A and B) exhibited quite poor antiangiogenic activities, whereas its B stereoisomer is more active than silybin A. The galloylation of phenolic OH groups of natural silybin (a mixture of both isomers) leads to increases in their antiangiogenic activities, which is more apparent with the 7-OH than the 20-OH. In contrast, gallates at aliphatic OH groups either had a comparable activity to the parent compound or are even worse than silybin, which was observed in the case of 3-O-galloylsilybin. The most effective compound from this series (7-O-galloylsilybin) has also been prepared from stereochemically pure silybins A and B to evaluate the effect of stereochemistry on the activity. As with silybin itself, the B isomer of 7-O-galloylsilybin was more active than the A isomer.
Keywords: buněčná diferenciace; vztahy mezi strukturou a aktivitou; Drug Combinations; proliferace buněk; Cell Differentiation; Humans; estery; Endothelial Cells; lidé; silymarin; Proteoglycans; stereoizomerie; endoteliální buňky; Cell Movement; endoteliální buňky pupečníkové žíly (lidské); Cell Proliferation; Structure-Activity Relationship; Silymarin; Esters; Laminin; pohyb buněk; kolagen; laminin; Angiogenesis Inhibitors; Stereoisomerism; inhibitory angiogeneze; Human Umbilical Vein Endothelial Cells; Collagen; Gallic Acid; kyselina gallová; proteoglykany; fixní kombinace léků